EMPLOYEE PERFORMANCE IN SERVICE UNDER LIMITED HUMAN RESOURCES - Erin Nur Putriani; Jenatul Firdausi; Riska Handayani (Lembaga Penerbitan, Penelitian, dan Pengabdian kepada Masyarakat (LP3M) of Institut Badri Mashduqi Probolinggo Jawa timur Indonesia, 2025)
This study examines employee performance analysis in providing services to prospective Umrah pilgrims at PT. Qiblatain Safarina Bakti under conditions of limited human resources. The background of the study is based on the significant increase in demand for Umrah services that requires travel agencies to continue to provide quality services, despite facing limitations in the number of available workers and competencies. This study uses a qualitative approach with data collection methods through interviews, observations, and literature studies from relevant references. The results show that limited human resources have an impact on workload imbalances and dual task practices that often cause stress for employees. Nevertheless, the company strives to maintain service quality through collaboration strategies, regular evaluations, competency improvement, and intensive communication with pilgrims. Further analysis reveals that motivation, skills, and the work environment are the main factors determining service quality. This study confirms that the constraint of limited human resources is not always an absolute obstacle. With adaptive management, these challenges can be minimized so that services remain consistent and professional. The implication of this research is the need for a strategy to strengthen human resource capacity, both through increasing the number of workers and improving skills, so that Umrah travel agencies are able to respond to the ever-growing demands of society.